Quantifying thermophysical properties, characterization, and thermal cycle testing of nano-enhanced organic eutectic phase change materials for thermal energy storage applications - Jacob, Jeeja; Kumar Pandey, Adarsh Kumar; Nasrudin, Abd Rahim; Selvaraj, Jeyraj; Paul Nadakkal, John; Samykano, Mahendran; Saidur, Rahman Md (Elsevier B.V., 2022)
Dispersion of highly conductive nanoparticles in Phase Change Materials (PCMs) tends to improve the thermophysical properties of nanocomposites. The current research condenses the synthesis, chemical, physical, and thermal characterization of novel nano-enhanced eutectic phase change materials (NeUPCMs) dispersed with TiO2 nanofillers for thermal management applications. The base matrix primarily comprises of a eutectic of paraffin wax and palmitic acid. Detailed analysis of the uncertainty of each thermophysical property measured was performed. The synthesized nanocomposite logged a maximal thermal conductivity of 0.59 W/mK (2.3-fold as compared with the base-0.25 W/mK) with 0.5% nanofillers. The composites displayed excellent solar transmissivity (82%) as they were doped with nanofillers having a high refractive index. The latent heat of the NeUPCMs got enhanced by 17% whereas the melting point showed a slight decrement in nanocomposites. Further, zero phase segregation, no subcooling, stable phase transition temperature, and good chemical, and thermal stability were noted from digital scanning calorimetry results with NeUPCMs. The composites exhibited good thermal reliability beyond 500 thermal cycles. It could be potentially deployed in the thermal management of medium-temperature systems like PVT and LCPVT systems.